1997
DOI: 10.1111/j.1525-1446.1997.tb00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use by Abused Women Following an Intervention Program: Associated Severity of Abuse and Reports of Abuse Ending

Abstract: Although violence against women is recognized as major public health problem, little is known about the effectiveness of interventions. To evaluate severity of abuse and use of community resources following an intervention program, 132 pregnant abused women received three counseling sessions in a prenatal setting. A comparison group of 67 abused women were offered a wallet-sized card listing community resources for violence. Resource use, severity of abuse, and reports of the abuse ending were measured for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 17 publications
5
78
0
Order By: Relevance
“…Women may not have felt comfortable reporting abuse or may not have considered their experiences as domestic violence. Although information on IPV perpetration was gathered from both self-report of arrest and arrest records, IPV perpetration on the whole is underrepresented because only one fourth to one half of IPV is reported to the police (McFarlane, Soeken, Reel, Parker, & Silva, 1997;Tjaden & Thoennes, 2000;U.S. Department of Justice, 1995) and only a portion of those results in arrest.…”
Section: Limitationsmentioning
confidence: 99%
“…Women may not have felt comfortable reporting abuse or may not have considered their experiences as domestic violence. Although information on IPV perpetration was gathered from both self-report of arrest and arrest records, IPV perpetration on the whole is underrepresented because only one fourth to one half of IPV is reported to the police (McFarlane, Soeken, Reel, Parker, & Silva, 1997;Tjaden & Thoennes, 2000;U.S. Department of Justice, 1995) and only a portion of those results in arrest.…”
Section: Limitationsmentioning
confidence: 99%
“…Problem-solving coping, on the other hand, has been related to well-being (Foa et al, 2000). Several studies document the variety of active coping strategies battered women use in response to abuse (Campbell & Gary, 1998;Goodman, Dutton, Weinfurt, & Cook, 2003;McFarlane, Soeken, Reel, Parker, & Silva, 1997). Social support has also been found to be a protective factor for battered women; it has been found to be related to reduced symptoms of PTSD (Astin, Lawrence, & Foy, 1993) and depression (Tan, Basta, Sullivan, & Davidson, 1995).…”
Section: Women's Coping With Violent Relationshipsmentioning
confidence: 99%
“…The only studies of advocacy interventions in women identified through screening in health-care services were based in antenatal clinics. 121,[131][132][133] The evidence for individual psychological interventions is sufficient according to the USPSTF criteria, but this is based on only three studies and, more so than the advocacy studies, the interventions are very heterogeneous. The evidence for group psychological interventions and that for mother and child programmes is insufficient as a basis for policy.…”
Section: Question Ii: Are Screening Tools Valid and Reliable?mentioning
confidence: 99%
“…[131][132][133] The women, attending an antenatal clinic, were offered an intervention of three brief sessions of individual advocacy (not described in any detail) -education, referral and safety planning -spread over their pregnancies. Additionally, half of the intervention group was offered three further support group sessions at a local refuge, but outcomes for these were not considered separately.…”
Section: Studies Included In Our Previous Reviewmentioning
confidence: 99%